THE QUESTION OF ENERGY AND CONSIDERATION OF ITS PLACE AND IMPORTANCE IN CLASSICAL AND NEOCLASSICAL THEORY OF GROWTH AND DEVELOPMENT - Kostić, Vladimir; Vučić, Ivana; Majstorović, Jovana (International Journal of Economic Practice and Policy, 2019)
Energy is crucial in all processes, including the process of economic growth. The process of economic growth involves the transformation of raw materials into the final product, which means the use of energy. The paper examines the importance of energy for contemporary economic development and points to the necessity to move from the use of non-renewable to the use of renewable energy resources. The undoubted connection between economic growth and energy consumption, as well as the divergent views of economic researchers regarding the causality of economic growth and energy consumption, was established, which is of crucial importance in the creation of energy policies of individual countries. The dominant position in economic science is confirmed by which the energy in classical theory is implicitly included in economic activity across the country as a key factor of production. On the contrary, in neoclassical economic theory energy was not recognized as an important productive factor, which at the same time represents one of its most pronounced weaknesses.
Keywords: neoclassical growth theory; classical growth theory; energy resources; economic development; energy; Economic Growth